Implied volatility asymmetries in currency options. - Lee, Swee Chee. (2008)
Previous studies find evidence of asymmetric risk-return relationship in the stock market. In this paper, we extend the studies by testing for the presence of asymmetry in the conditional relationship between the perception of risk, proxied by the implied volatility of over-the-counter currency options, and the contemporaneous conditions of the currency market.